2012
DOI: 10.4103/0973-1482.98968
|View full text |Cite
|
Sign up to set email alerts
|

Micronuclei assay of exfoliated oral buccal cells: Means to assess the nuclear abnormalities in different diseases

Abstract: The micronuclei assay (MA) in exfoliated buccal cells is an innovative genotoxicity technique, which holds promise for the study of epithelial carcinogens. Micronuclei are suitable internal dosimeters for revealing tissue-specific genotoxic damage in individuals exposed to carcinogenic mixtures. This article reviews the MN assay with respect to oral buccal mucosa, which has been used since the 1980s to demonstrate cytogenetic effects of environmental and occupational exposures, lifestyle factors, dietary defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 0 publications
3
81
0
5
Order By: Relevance
“…6 Several studies have been conducted on micronuclei assay on the exfoliated cells of buccal mucosa of diabetic patients and have found that the frequency of micronuclei was increased in diabetic patients as compared to the normal individuals. Our results were consistent with the similar study conducted by Shashikala et al, 6 Kashyap and Reddy, 7 Holland et al, 8 which showed increased prevalence of micronuclei in diabetic patients as compared to the normal individuals. One of the parameters considered for the study was enlarged nuclei.…”
Section: Discussionsupporting
confidence: 93%
“…6 Several studies have been conducted on micronuclei assay on the exfoliated cells of buccal mucosa of diabetic patients and have found that the frequency of micronuclei was increased in diabetic patients as compared to the normal individuals. Our results were consistent with the similar study conducted by Shashikala et al, 6 Kashyap and Reddy, 7 Holland et al, 8 which showed increased prevalence of micronuclei in diabetic patients as compared to the normal individuals. One of the parameters considered for the study was enlarged nuclei.…”
Section: Discussionsupporting
confidence: 93%
“…The micronuclei were counted according to criteria given by Tolbert et al 12 The micronucleated cell frequency was calculated and the data obtained were subjected to statistical analysis. Only 1 out of 10 cases showed positivity with both Feulgen and Pap stain in control group, and in SCC, all cases showed positivity for micronuclei ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The MN test is a noninvasive, cost-effective, and easily acceptable procedure by patients. [10][11][12] Based on this background, this study was undertaken to identify the feasible and economical method that could be used as a screening test in high-risk population for identifying the effects of genomic instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Embora os dados da literatura não demonstrem relação entre o sexo e a ocorrência dos parâmetros indicadores de genotoxicidade e citotoxicidade 28 , em nossas investigações, observamos maior frequência de brotamentos entre os homens do grupo controle.…”
Section: Grupo De Influênciaunclassified